2018
DOI: 10.4236/nr.2018.910021
|View full text |Cite
|
Sign up to set email alerts
|

Linking Local Appreciation with Conservation of an Edible Fruit Species: The Case Study of Ilama (<i>Annona diversifolia</i> Saff.) in Tierra Caliente, Mexico

Abstract: The ilama tree (Annona diversifolia Saff.) is an underutilized fruit species from Mesoamerica with a noteworthy variability in southern Mexico. The present study describes differences in knowledge and appreciation of the fruit among inhabitants from different communities in Southern Mexico, as well as differences among their ilama trees. The study took place in Tierra Caliente, a region located in the states of Guerrero and the State of Mexico. Interviews were administered in three different communities as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Ilama has become one of the best known, commercialized and extensively studied species in recent years considering its therapeutic potential and traditional use. The fruit of this plant is used as food, but its leaves are a waste product at the agro-industrial level [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ilama has become one of the best known, commercialized and extensively studied species in recent years considering its therapeutic potential and traditional use. The fruit of this plant is used as food, but its leaves are a waste product at the agro-industrial level [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is important to highlight that several studies of different extracts obtained from ilama leaves have shown that they possess flavonoid glycosides, acyclic sesquiterpenoids and an aliphatic ketone. In the case of pharmacological studies, ilama leaves exhibited anxiolytic, antinociceptive, anticonvulsant, antihyperglycemic and antiepileptic effects [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%